Bentuk Jiwa Nasionalisme yang Tercermin pada Siswa Generasi Z di Sekolah Menengah Atas Indonesia - Adella Dianprila Putritama; Puji Hardati; Hamdan Tri Atmaja (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
National character is a fundamental foundation for fostering nationalism among Generation Z students who grow up in a highly digitalized and globally connected environment. Continuous exposure to global information may weaken students’ awareness of national identity if not balanced by structured character education. This study aims to describe the forms of nationalism reflected in the attitudes, behaviors, and participation of Generation Z students in Indonesian senior high schools. Using a descriptive qualitative approach, the research was conducted in a public and a private senior high school. Data were collected through observations, semi-structured interviews, and document analysis involving Grade X students as primary participants, supported by teachers, school leaders, and extracurricular advisors. The data were analyzed thematically to identify patterns and contextual differences. The findings indicate that students’ nationalism is manifested through values of unity, solidarity, responsibility, independence, and willingness to contribute to collective activities. While public schools emphasize formal and periodic programs, private schools apply more contextual and daily-based practices. Overall, both contexts demonstrate the importance of national character education in sustaining students’ nationalism amid global influences. However, this study is limited by its restricted research scope, as data were collected from only two schools, which constrains the broader generalizability of the findings. In addition, the focus on Grade 10 students does not fully capture the dynamics of nationalism across all senior high school grade levels.